2010
DOI: 10.1007/s10842-010-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tax and Public Ownership in Vertically Related Markets

Abstract: This paper investigates the optimal rate of environmental tax and level of privatization in a vertical relationship between one partially privatized producer and two private sellers. The main results are as follows: First, privatization of the producer firm decreases environmental damage. Second, the optimal environmental tax rate equals the Pigouvian level. Third, fully nationalizing the producer firm is optimal when the government simultaneously decides upon the environmental tax rate; then, privatization de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…The above proposition is in contrast to many of the existing papers such as Beladi and Chao (2006), Ohori (2012), Naito and Ogawa (2009) and . In contrast to these papers we show that when the products are differentiated and the public firm is unconcerned about environment, privatization can further damage the environment, if privatization is still below a critical level.…”
contrasting
confidence: 64%
See 2 more Smart Citations
“…The above proposition is in contrast to many of the existing papers such as Beladi and Chao (2006), Ohori (2012), Naito and Ogawa (2009) and . In contrast to these papers we show that when the products are differentiated and the public firm is unconcerned about environment, privatization can further damage the environment, if privatization is still below a critical level.…”
contrasting
confidence: 64%
“…However, these models ignored abatement measures, and of course output competition. Ohori (2012) extends this framework to vertical relationship. Cato (2008) have demonstrated that desirability of mixed oligopoly over private oligopoly depends on the extent of negative externalities generated through production.…”
Section: Barcena-ruiz Andmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that the solutions are interior 1 0 c t − − > and 1 0 c ψ − − > . Following Beladi and Chao [2] and Ohori [6], firm 0 's objective function is defined as the sum of the consumer surplus and the producer surplus (i.e., profits of both the firms) and is given by…”
Section: The Modelmentioning
confidence: 99%
“…A number of studies have focused on optimal emission taxes under imperfect competition 3 . Taxing emissions in order to reduce social damage 1 Refer Bàrcena-Ruiz and Garzòn [1], Beladi and Chao [2], Kato [3], Naito and Ogawa [4], and Ohori [5] [6] for environmental policies in the markets of public firms. 2 Recent papers that have examined the endogenous choice between price and quantity strategies in a mixed oligopoly include Matsumura and Ogawa [7] and Nakamura [8].…”
Section: Introductionmentioning
confidence: 99%